Synthesis of New Five-Membered Hetrocyclic Compounds from 2-Furfuryl Mercaptan Derivative and Evaluation of their Biological Activity - Luma S. Ahamed (Journal of Global Pharma Technology, 2018)
Sixteen compounds were synthesized from 2- furfuryl mercaptan as starting material which was reacted with ethyl chloroacetate to produce 2-furfuryl mercaptan ester derivative. The later was reacted  with hydrazine hydrate to  produce hydrazide derivative(2)which was introduced in different synthetic methods by using either cyclization reactions or  using  different reagents to produce biheterocyclic  systems(3-16).Keyword: Five-membered heterocycles, 2-furfuryl mercaptan, Biological activity.